The Long-Term Burden of COPD Exacerbations During Maintenance Therapy and Lung Function Decline - Kerkhof M; Voorham J; Dorinsky P; Cabrera C; Darken P; Kocks JWH; Sadatsafavi M; Sin DD; Carter V; Price DB (International Journal of COPD, 2020)
Marjan Kerkhof,1 Jaco Voorham,1 Paul Dorinsky,2 Claudia Cabrera,3,4 Patrick Darken,5 Janwillem WH Kocks,1,6 Mohsen Sadatsafavi,7,8 Don D Sin,7,8 Victoria Carter,1 David B Price1,9 1Observational & Pragmatic Research Institute Pte Ltd, Singapore, Singapore; 2AstraZeneca, Durham, NC, USA; 3AstraZeneca, Mölndal, Sweden; 4Department of Medical Epidemiology and Biostatistics, Karolinska Institute, Stockholm, Sweden; 5AstraZeneca, Morristown, NJ, USA; 6General Practitioners Research Institute, Groningen, The Netherlands; 7Respiratory Evaluation Sciences Program, Collaboration for Outcomes Research and Evaluation, University of British Columbia, Vancouver, BC, Canada; 8Centre for Heart Lung Innovation, St. Paul’s Hospital, Vancouver, BC, Canada; 9Academic Primary Care, University of Aberdeen, Aberdeen, UKCorrespondence: David B Price Polwarth Building, Foresterhill, Aberdeen AB25 2ZD, UKTel +65 6962 3627Email dprice@opri.sgIntroduction: Early identification of preventable risk factors of COPD progression is important. Whether exacerbations have a negative impact on disease progression is largely unknown. We investigated whether the long-term occurrence of exacerbations is associated with lung function decline at early stages of COPD.Methods: Patients diagnosed with mild/moderate COPD (obstruction and FEV1% predicted 50– 90%), aged ≥ 35 years, and a smoking history, who had ≥ 6 years of UK electronic medical records after initiation of maintenance therapy were studied. Multilevel mixed-effect linear regression was performed to determine the association between the count of any year in which the patient had ≥ 1 exacerbation over a 6-year period and FEV1 decline, adjusted for sex, age, anthropometrics and smoking habits. Exacerbations were defined as any prescription for an acute oral corticosteroid course and/or lower respiratory-related antibiotics and/or any COPD-related emergency or inpatient hospitalization.Results: Of 11,337 patients included (mean age 65 years; 49% female) 31.6%, 23.3%, 16.6%, 11.6%, 8.1%, 5.3% and 3.4% had 0, 1, 2, 3, 4, 5 and 6 years with ≥ 1 exacerbation. The mean annual FEV1 decline accelerated by 1.50 mL/year (95% Confidence Interval 1.02; 1.98) with every additional year with ≥ 1 exacerbation from 31.0 mL/year in subjects without any exacerbation to 40.0 mL/year in patients experiencing ≥ 1 exacerbation every year. Patients with more years with ≥ 1 exacerbation had a lower mean FEV1 at first diagnosis: 14.7 mL (11.7; 17.8) lower with every additional year with exacerbations. When counting years with ≥ 2 exacerbations, greater effects were observed (2.19 [1.50; 2.88]  mL/year excess decline per year with ≥ 2 exacerbations; 16.5 mL [12.1; 20.8] lower FEV1 at diagnosis).Conclusion: Patients who experienced a greater exacerbation burden after initiation of maintenance therapy had worse lung function at diagnosis and a more rapid lung function decline thereafter, which emphasizes the need for better treatment strategies.Keywords: COPD, exacerbations, spirometry, inhalation therapy, observational study